PERFORMANCE AYAM BROILER DENGAN PERKANDANGAN SISTEM CLOSED HOUSE DAN CLOSED HOUSE BERBASIS IoT (INTERNET OF THINGS) DI PT.INTEGRASI TEKNOLOGI UNGGAS YOGYAKARTA - Manullang, Julinda Romauli; Laksono, Bayu Agung; Fajrih H, Nurul; anindyasari, dinar (Universitas Djuanda, 2024)
The purpose of this research was to determine the difference in the effect of closed-house cages based on IoT (Internet of Things) and closed-house cages on broiler chicken performance, feed consumption, body weight gain, FCR, final body weight and mortality. The results of testing calculations and data processing of feed consumption in the GAD Farm cages showed that the IOT-based closed house cages were 907.6 g/head and in closed house cages 770 g/head. The increase in body weight obtained from closed house cages based on IOT was 522.8 g/head and in closed house cages the result was 434.81 g/head. Feed conversion results obtained from IOT-based closed house cages were 1.2 and closed house cages were 1.32. The temperature and humidity of the IoT-based closed house enclosure obtained an average temperature of 28.2˚ C with humidity of 84.2%. Closed house cages obtained an average temperature of 28.9˚C with humidity of 86.8%. final body weight or harvest during the broiler chicken rearing period, the average final body weight in the IOT-based closed house was 1,084.52 g/head and the closed house at GAD Farm was 1,040.75 g/head and the mortality value was 2.27% ; and the highest death occurred in the first week with 318 chickens. As for the lowest mortality, it was found in IoT-based closed house cages with a value of 2.914%. The conclusion of this research shows that the performance analysis results of IoT-based Closed House cages tend to be higher compared to Closed House cages at GAD Farm.